Sequence and expression analysis of glucokinase mRNA from herbivorous Giant gourami (Osphronemus goramy) - Dian Novita Sari; Hasan Nasrullah; Julie Ekasari; Muhammad Agus Suprayudi; Alimuddin Alimuddin (Society for Indonesian Biodiversity, 2021)
Abstract. Sari DN, Nasrullah H, Ekasari J, Suprayudi MA, Alimuddin A. 2021. Sequence and expression analysis of glucokinase mRNA from herbivorous Giant gourami (Osphronemus goramy). Biodiversitas 22: 741-750. Glucokinase (GCK) is one of the enzymes that play important roles in carbohydrate metabolism and high glucose homeostatic in fish. The information about the GCK mRNA sequence and its expression is limited in Giant gourami, one of the most important herbivorous aquaculture species in Indonesia. The present study aimed to characterize the GCK mRNA and analyze its mRNA expression and plasma glucose levels after high glucose injection in Giant gourami. We also compared its sequence variability among carnivorous and herbivorous fish. The GCK mRNA was identified using polymerase chain reaction (PCR) method from the fish liver. Its mRNA level was analyzed by real-time PCR (qPCR). Giant gourami GCK mRNA sequence was 2104 nucleotide long, encoding 478 amino acids, and shared high similarity with other fish. GCK was mainly expressed in the liver. The mRNA level of GCK was highly up-regulated after 6 hours of high glucose injection, in-line with the plasma glucose in the blood. There are no major differences observed in the GCK amino acid sequences among Giant gourami and other fish. The knowledge gained from this study could be used as a reference for further exploration of metabolic regulation in Giant gourami.